Profitability Ratios Analysis in Telecommunication Industry Before, During, and After Covid Pandemic - Putri, Gianisa Mentari; Widyarini, Maria; Dewi, Vera Intanie (FIA UB, 2025)
The COVID-19 pandemic has significantly disrupted the business landscape due to the implementation of PSBB policies. The pandemic restricted activities in areas affected by the virus, resulting in substantial changes in consumer behaviour. There was a surge in demand for telecommunications products and services as individuals and businesses adapted to remote work and online interactions. These changes have positively impacted the financial performance of telecommunications companies. However, these companies face challenges in operations and principles. ESG encompasses social and environmental responsibility and ethical corporate governance that affect their profitability. Profitability assesses a company's ability to generate revenue from operations using gross profit margin, net profit margin, return on assets, and return on equity. Other analytical techniques have also been used, such as horizontal analysis, which compares data across periods, and vertical analysis, which evaluates components of financial statements. This study also uses variance analysis, trend analysis, and documentation on secondary data. 2019 to 2023: The financial statements of four major telecommunications companies are the samples used in this study. This study shows that gross profit margin, net profit margin, return on assets, and return on equity have significant differences or similarities before, during, and after the pandemic.